2023
DOI: 10.1038/s41598-023-37403-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between radioactivity and toxicity in some medicinal plants

Eman H. Abdelfadeel,
E. S. Abd El-Halim,
T. M. Hegazy
et al.

Abstract: Plants absorb water, nutrients and minerals from the soil through their root. Also, minerals, the radionuclides present in the growing media also are absorbed by plant parts following the same pathway. Consequently, it is important to determine the concentrations of these radionuclides in edible plants to access the associated risk to human health. In the present work, the levels of natural radioactivity and the level of some toxic elements in 17 medicinal plants, commonly used in Egypt, were measured using hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the case of herbal plants, which are often consumed or used in infusions as part of a daily diet, it is crucial to determine their effect on human health. This is particularly important since studies have shown that certain parts of the plant, especially leaves, could be highly contaminated with radionuclides (Abdelfadeel et al, 2023;Desideri et al, 2010Desideri et al, , 2011Kovács et al, 2015;Moniakowska et al, 2020;Monica et al, 2020;Narayana & Prakash, 2007;Olszewski et al, 2019;Puchkova & Bogdanova, 2015Shuaibu et al, 2023;Skwarzec et al, 2001;Sussa et al, 2013). Therefore, there is a need to monitor the radionuclide composition of plants harvested in Ukraine for medicinal purposes.…”
Section: Core Ideasmentioning
confidence: 99%
“…In the case of herbal plants, which are often consumed or used in infusions as part of a daily diet, it is crucial to determine their effect on human health. This is particularly important since studies have shown that certain parts of the plant, especially leaves, could be highly contaminated with radionuclides (Abdelfadeel et al, 2023;Desideri et al, 2010Desideri et al, , 2011Kovács et al, 2015;Moniakowska et al, 2020;Monica et al, 2020;Narayana & Prakash, 2007;Olszewski et al, 2019;Puchkova & Bogdanova, 2015Shuaibu et al, 2023;Skwarzec et al, 2001;Sussa et al, 2013). Therefore, there is a need to monitor the radionuclide composition of plants harvested in Ukraine for medicinal purposes.…”
Section: Core Ideasmentioning
confidence: 99%